Caracterisation de quelques parties precompactes dans les treillis vectoriels localement convexes et solides - B. Aqzzouz; R. Nouira (Հայաստանի ԳԱԱ)
By using the pre-Lebesque topology, the paper points at some relations between several notions of precompact subsets in a locally solid and convex vector lattice.
Keywords: Mathematics; Science